Additions to the genus Hemacroneuria Enderlein (Plecoptera: Perlidae) from China - Li, Weihai; Mo, Raorao; Murányi, Dávid (Zootaxa, 2019)
Two new species of the perlid genus Hemacroneuria Enderlein, 1909, H. elongata sp. nov. and H. ovalis sp. nov. are described from Sichuan and Zhejiang provinces of China, respectively. A poorly known Sichuan species, H. spatulata (Wu 1948) comb. nov. is transferred from Kiotina Klapálek, 1907 to Hemacroneuria, and an additional species known only from a female is reported by an informal designation. Aedeagal structures of Hemacroneuria males are described in detail for the first time and are useful for the separation of the genus from other genera of the Acroneuriinae. The taxonomic relationships of the new species are discussed.